Theoretical analysis and experimental results on the modulated photocarrier grating technique - Schmidt, Javier Alejandro (2010)
We present a complete theoretical analysis of the modulated photocarrier grating method (MPG). Our calculations show that the response of the sample will be not only a photocurrent modulated with the frequency f of the illumination, but also a response in dc and with frequency 2f. In order to put to test our calculations, we implement experimentally the MPG technique and we apply it to a hydrogenated amorphous silicon sample. We verify the existence of a response at frequency 2f, and we measure the relative intensity of this signal ? which compares well with the result of our theoretical calculation. We also show that under certain conditions the density of states (DOS) at the quasi-Fermi level for the majority carriers is related to the ratio of the MPG and modulated photoconductivity (MPC) signals. We present a simple formula that allows estimating the DOS as a function of energy by changing the temperature and the generation rate.